Streamlining OS/DB Migrations for SAP Environments: A Comparative Analysis of Tools and Methods - Bhatt, Sachin; Narne, Suman (Stallion Journal for Multidisciplinary Associated Research Studies, 2023)
An evaluation of various tools and activities in the process of the OS/DB migrations in SAP context is the goal of this research paper. They assess the major instruments that are SAP Software Update Manager (SUM) together with Oracle Goldengate and migration approaches like Standard Migration also, Near-Zero Downtime Migration (NZDM). Each of the tools is described in terms of the features it offers, advantages, and disadvantages it has in comparison with the other tools, and the real-life applications of the tools are analysed. Examples include best practice examples, which point out and explain both opportunities and issues. The paper concludes by reiterating key points, as well as general factors to bear in mind during an actual migration such as planning, selecting tools, testing the migration, and support during and after migration. The findings contribute to the body of knowledge useful in enhancing OS/DB migration plans in SAP systems.